Estudo farmacológico e auto-radiográfico do complexo GABAA/Sítio benzodiazepínico, e ensaios bioquímicos da enzima Na+/K+- Atpase e de receptores glutamatérgicos em regiões encefálicas de ratos susceptíveis e não-susceptíveis às convulsões clônicas induzidas pelo DMCM, um agonista inverso benzodiazepínico - Contó, Marcos Brandão [UNIFESP] (2009)
Objective: The aim of this work was to verify if rats susceptible and non-susceptible to clonic convulsions induced by DMCM, a benzodiazepine inverse agonist, differ: 1) in the sensitivity to the hypnotic effect induced by diazepam and by others positive allosteric modulators of GABAA receptors; 2) in auto-radiographical analysis of [3H]-flunitrazepam binding along the brain; 3) in the binding of [3H]-L-glutamate and of [3H]-MK 801 in membranes from discrete brain regions; and 4) in the Na+/K+-ATPase activity, as well as in the binding of [3H]-ouabain to Na+/K+-ATPase isoenzimes with high and low affinity to the radioligand in membranes from discrete brain regions. Methods: Adult, male, Wistar rats were administered with two intraperitoneal injections of a convulsant dose 50% (CD50) of DMCM (one-week interval between them), resulting in two distinct groups: the group susceptible to clonic convulsions (SC), which presented clonic convulsions in both the expositions to the drug, and the group nonsusceptible to clonic convulsions (NSC), which did not present any motor disturbance in both the expositions. After 25 days from the second exposition to DMCM, the selected groups were submitted to the experiments with the hypnotics diazepam, pentobarbital and ethanol, in which were registered the latency and the time of sleep or they were sacrified and their brains were removed to carry out the following assays: 1) autoradiography with [3H]-flunitrazepam; 2) binding with the [3H]-L-glutamate and with the [3H]-MK 801 in neuronal membranes; 3) enzymatic activity of Na+/K+-ATPase and binding of [3H]-ouabain to the isoenzimes with high and low affinity in neuronal membranes. Results: The SC group presented a lower sleeping time induced by diazepam compared to the NSC group, and did not differ in the sleeping time induced by pentobarbital and ethanol. Concearning the biochemical experiments, it was observed a lower binding of [3H]-flunitrazepam in the CA2 subregion of ventral hippocampus in the SC group. A lower binding of [3H]-L-glutamate was also observed in the SC group in the frontal cortex, amygdala plus limbic cortex and hippocampus, whereas the binding of [3H]-MK 801 was lower in the frontal cortex, hippocampus and striatum compared to the NSC group. Althougt the groups did not differ in the enzymatic activity of Na+/K+- ATPase, the SC group presented a lower binding of [3H]-ouabain to the high-affinity isoenzimes in the brainstem, frontal cortex and hippocampus, as well as a lower binding of [3H]-ouabain to the low-affinity isoenzimes in the brainstem and in the frontal cortex compared to the NSC group. Conclusion: The differences between the groups concerning the sensitivity to the convulsant effect of DMCM, the level of anxiety previously observed, as well as the sensitivity to the hypnotic effect of diazepam may be associated with the GABAA/benzodiazepine site in CA2 subregion of ventral hippocampus, with glutamatergic activity and with specific isoforms of Na+/K+-ATPase in rat brain regions.